LONTAR USADA RARE: MEMAHAMI KEARIFAN LOKAL TRADISIONAL BALI DALAM MENDIAGNOSA GEJALA PENYAKIT ANAK - Adnyana, Putu Eka Sura (Institut Hindu Dharma Negeri Denpasar, 2020)
Family problems become very crucial at this time due to the absence of family planning. Various reactions are shown by parents when the child is experiencing an illness. Not a few maidset parents who think that when a child is sick must be immediately taken to the doctor to get treatment and treatment through drugs. The disease diagnosis system accompanied by traditional treatments in Bali is known as Usada. One of them is usada rare papyrus is a papyrus that discusses the symptoms of disease in children and how to treat it in children. Lontar usada rare text describes the symptoms of illness experienced by a child, including upas disease, tiwang disease, sebaha disease, spells, scales, and other groups of diseases. Recognizing and understanding the symptoms of the disease based on the Usada Rare Lontar provides an early understanding of the symptoms of the disease in children through traditional Balinese diagnosis in a papyrus record.